2021
DOI: 10.1002/ana.26131
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Risk Score for Alzheimer's Disease in Caribbean Hispanics

Abstract: Objective Polygenic risk scores (PRSs) assess the individual genetic propensity to a condition by combining sparse information scattered across genetic loci, often displaying small effect sizes. Most PRSs are constructed in European‐ancestry populations, limiting their use in other ethnicities. Here we constructed and validated a PRS for late‐onset Alzheimer's Disease (LOAD) in Caribbean Hispanics (CH). Methods We used a CH discovery (n = 4,312) and independent validation sample (n = 1,850) to construct an anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…Significance of the contrast between LOAD and non-LOAD status (LOAD vs. control for Mayo) was performed using empirical Bayes moderation (eBayes function). We meta-analyzed differential expression results from the three TWAS employing a fixed-effect model and using logFC and its standard error (SE) as inputs, consistently with previous studies of transcriptomics in LOAD [36,43,44]. The SE was calculated from the logFC values for each gene, separately in each cohort, and used for standard meta-analysis using the R package "rmeta".…”
Section: Ad Transcriptome-wide Association Studies (Twas) and Meta-analysismentioning
confidence: 99%
“…Significance of the contrast between LOAD and non-LOAD status (LOAD vs. control for Mayo) was performed using empirical Bayes moderation (eBayes function). We meta-analyzed differential expression results from the three TWAS employing a fixed-effect model and using logFC and its standard error (SE) as inputs, consistently with previous studies of transcriptomics in LOAD [36,43,44]. The SE was calculated from the logFC values for each gene, separately in each cohort, and used for standard meta-analysis using the R package "rmeta".…”
Section: Ad Transcriptome-wide Association Studies (Twas) and Meta-analysismentioning
confidence: 99%
“…Separately, Sariya et al highlighted differences in the relative contributions of APOE genotype and PRS between CH and non‐Hispanic Whites for AD. They found that the PRS seems to play a bigger role in predicting LOAD in the CH population 6 suggesting that further refinement of PRS in future studies may be useful, though the functional significance of these variances was not addressed in their investigations. A recent study in an African‐American population involving 25 known loci linked with AD in non‐Hispanic Whites revealed that only APOE and six other loci showed significant association.…”
mentioning
confidence: 96%
“…Since the heritability of AD and PD for most cases remains unaccounted for and most of the large scale genome wide association studies (GWAS) have focused on subjects with European‐ancestry, 3,4 there is a need for such studies in other ethnicities to identify novel loci/variants and to validate established ones. In this light, two timely studies by Loesch and colleagues and by Sariya and coworkers in this issue attempted to address some of the knowledge gaps in the genetic architecture of AD and PD in Caribbean Hispanics (CH) and Latinos 5,6 …”
mentioning
confidence: 99%
See 2 more Smart Citations